Setting time and heat of hydration of wastepaper sludge ash-ground granulated blastfurnace slag blended cements - A. Chaipanich (2018)
This paper reports the results of an investigation of the setting times and heats of hydration of WSA-GGBS and WSA-GGBS-PC blended pastes. Setting time tests were carried out in accordance with BS EN 196-3 and also at a constant w/b ratio (0.5). Regardless of the test procedure used, the setting times of WSA-GGBS blended pastes were found to decrease with increasing WSA content. Gypsum and a plasticiser/retarder admixture were used to extend the initial setting time in order to aid mixing and casting of pastes. The latter was found to effectively extend the initial setting time similar to that of the PC pastes. However, it is apparent that only a small dosage is required and overdosing can lead to excessive retardation of the final set. Heat evolution results of WSA-GGBS pastes show that more heat is produced and the rate of heat evolution also increased with increasing WSA content.